Transfer of training in an academic leadership development program for program coordinators - Ladyshewsky, Richard; Flavell, Helen (Sage Publications, 2012)
The higher education sector has increasingly begun to pay more attention to academic leadership. This qualitative study explores how such an investment in a 20-week leadership development program influenced the behaviour of 10 academic staff in the role of program coordinator 6 to 12 months following participation in the program. Otherwise known as program directors or department chairs, academic staff in this role are responsible for coordinating and leading degree courses or programs. Leadership learning and changes in the behaviour of program coordinators was evident, particularly in regard to building influence, communicating more effectively and managing upwards. Improved confidence in their ability to perform the role was a lasting outcome and the use of peer learning and coaching was an important part of the success of the intervention. However, workload factors, succession planning and orientation were seen to be factors that impact on leadership development in this role. The findings suggest that participation in well designed academic leadership programs can result in a lasting transfer of training for program coordinators.